Risk Analysis of Lead (Pb) in Anadara granosa from the Waters of North Penajam Paser - Saputra, Muhammad Ikhsan; Nurfadilah, Nurfadilah; Ritonga, Irwan Ramadhan (Jurnal Biologi Tropis, 2025)
Blood clam (Anadara granosa), a widely consumed filter-feeder in the coastal waters of Babulu Laut, East Kalimantan, has a high potential to accumulate lead (Pb) from its environment. This study aimed to determine the concentration of Pb in A. granosa and assess the potential health risks to humans associated with the consumption of A. granosa. A total of 45 A. granosa were caught by local fishermen. Each mussel was measured for length, destroyed using an acid method, and analysed using Atomic Absorption Spectrophotometry (AAS). The results of the study found that Pb concentrations ranged from 0.114 to 0.148 mg/kg dry weight. The Pb concentration in mussels was still below the maximum limit permitted by the Indonesian National Standard (SNI 7387:2009). The health risk assessment results found that the EWI value was relatively lower than the PTWI and the HQ value was lower than 1, indicating that there was not non-carcinogenic risk to consumers. Furthermore, the average cancer risk (TR) to consumers, including adults, adolescents and children, was low. Even though the Pb concentration was below the quality threshold, consumers may still need to be cautious about consuming A. granosa sourced from the coastal waters of Babulu Laut.